Indigenising and Africanising South Africa's Approaches to Curbing COVID-19 in South Africa: An Integrated Approach. Issue 1 (2nd January 2022) - Makanda, Joseph; Matambo, Emmanuel
Abstract: South Africa's declaration of a state of pandemic on 27 March 2020 to combat the spread of the novel coronavirus disease (COVID-19) has elicited debates on the impact of government's policy responses, such as national lockdowns, on the economy of the country. Some pundits support lockdown measures by arguing that they save many lives. Others acknowledge the efficacy of lockdowns in combating the spread of COVID-19 but argue that they have a devastating impact on the economy and livelihoods. However, both pro- and anti-lockdown commentators neglect African indigenous approaches in combatting the spread of infectious diseases such as COVID-19. The current paper offers a consolidated approach on how African indigenous approaches might be practically and pragmatically integrated with South Africa's COVID-19 policy responses. Drawing on Afrocentric theory, this paper argues that a combination of Western and African indigenous approaches can be more successful in combating the spread of COVID-19 if they are incorporated into a synthesis that adopts useful elements of each. This paper argues that by insisting on national lockdowns, social distancing, self-isolation, and the use of facemasks and vaccines as the only means of combating COVID-19, the South African government is discrediting the use of indigenous African knowledge.